2021
DOI: 10.1017/s1041610220004019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Reitman Centre CARERS program for supporting dementia family caregivers: a pre–post intervention study

Abstract: Objectives: While family caregivers (CGs) of persons with dementia are cost-effective for the health system, this form of caregiving leads to disproportionate vulnerability to physical, mental, and social adverse health consequences among CGs. The study goal was to determine the effect of the Reitman Centre CARERS program on key outcomes in family CGs of people with dementia. The Reitman Centre CARERS program is an innovative, group psychotherapeutic skills training intervention based on integrated proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 63 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…Additionally, this design was considered a valid method to conduct research on caregiver program efficacy. 24 In this study, we included both an intervention and a control group, as described below.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, this design was considered a valid method to conduct research on caregiver program efficacy. 24 In this study, we included both an intervention and a control group, as described below.…”
Section: Methodsmentioning
confidence: 99%
“…One example of our suite of training programmes is the CARERS programme, originally developed for caregivers of PwD in Canada. CARERS was shown to produce sustained improvement in caregivers' perceived stress, mastery, depressive symptoms, caregiving competence and coping, key qualities needed to support the caregivers' capacity to continue in their caregiving role for the foreseeable future (Sadavoy et al, 2021). When this approach was piloted locally, the caregivers who attended the training reported that they were able to apply its lessons to their day‐to‐day management of the PwD.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we developed the Dementia Caregiver Interview Guide (DCIG) at The Cyril & Dorothy, Joel & Jill Reitman Centre for Alzheimer Support and Training ("Reitman Centre") at Sinai Health, a University of Toronto Academic Health Sciences Centre in Toronto, Canada. As part of the Geriatric Psychiatry Program at the hospital, the Reitman Centre has developed an array of multidimensional approaches to provide evidence-based skills training and therapeutic support for family caregivers who are caring for individuals with dementia [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%